Diagnostic biomarkers for active tuberculosis: progress and challenges - Betânia M F Nogueira; Sonya Krishnan; Beatriz Barreto‐Duarte; Mariana Araújo‐Pereira; Artur T L Queiroz; Jerrold J Ellner; Padmini Salgame; Thomas J Scriba; Timothy R Sterling; Amita Gupta; Bruno B Andrade (EMBO Molecular Medicine)
Abstract Tuberculosis (TB) is a leading cause of morbidity and mortality from a single infectious agent, despite being preventable and curable. Early and accurate diagnosis of active TB is critical to both enhance patient care, improve patient outcomes, and break Mycobacterium tuberculosis (Mtb) transmission cycles. In 2020 an estimated 9.9 million people fell ill from Mtb, but only a little over half (5.8 million) received an active TB diagnosis and treatment. The World Health Organization has proposed target product profiles for biomarker‐ or biosignature‐based diagnostics using point‐of‐care tests from easily accessible specimens such as urine or blood. Here we review and summarize progress made in the development of pathogen‐ and host‐based biomarkers for active TB diagnosis. We describe several unique patient populations that have posed challenges to development of a universal diagnostic TB biomarker, such as people living with HIV, extrapulmonary TB, and children. We also review additional limitations to widespread validation and utilization of published biomarkers. We conclude with proposed solutions to enhance TB diagnostic biomarker validation and uptake.